Light diffuseness metric Part 1: Theory. (June 2017) - Xia, L; Pont, SC; Heynderickx, I
The light density, direction and diffuseness are important indicators of the spatial and form-giving character of light. Mury presented a method to describe, measure and visualise the light field's structure in terms of light density and direction variations in three-dimensional spaces. We extend this work with a theoretical and empirical review of four diffuseness metrics leading to a novel metric proposal DXia . In particular, the relationships between these diffuseness metrics were studied using a model named 'probe in a sphere'. Diffuseness metric DXia re-frames the diffuseness metric of Cuttle in an integral description of the light field. It fulfils all diffuseness criteria and has the advantage that it can be used in a global, integrated description of the light flow and diffuseness throughout three-dimensional spaces.